Happier with Vocational Education? - Giorgio Brunello (Institute of Labor Economics (IZA), 2020)
Using Italian data, I study the relationship between vocational education and self-reported happiness by focusing on individuals with at least a five-years high school degree, either vocational or academic. My instrumental variable strategy shows that individuals who have completed a vocational high school are more likely to report a high level of happiness than individuals who have completed an academic degree. I find no clear evidence that vocational graduates have a lower probability to be employed or earn lower wages than other graduates. I show that they live more than other graduates in small towns, where prices are lower and social life more rewarding, and have a less privileged parental background. Both facts may lead to more moderate aspirations and therefore contribute to higher happiness.
Keywords: I21; D90; 330; happiness; vocational education; Italy